Microneme Proteins 1 and 4 From Toxoplasma gondii Induce IL-10 Production by Macrophages Through TLR4 Endocytosis - Ricci-Azevedo, Rafael; Mendonça-Natividade, Flavia Costa; Santana, Ana Carolina; Alcoforado Diniz, Juliana; Roque-Barreira, Maria Cristina (Frontiers in Immunology, 2021)
The protozoan parasite Toxoplasma gondii modulates host cell responses to favor its success in the early stage of infections by secreting proteins from its apical organelles. Some of these proteins, including microneme proteins (MICs) 1 and 4, trigger pro-inflammatory host cell responses. The lectins MIC1 and MIC4 interact with N-linked glycans on TLR2 and TLR4, activating NF-κB and producing IL-12, TNF-α, and IL-6. Interestingly, MIC1 and MIC4 also trigger secretion of the anti-inflammatory cytokine IL-10 through mechanisms as yet unknown. Herein, we show that the ability of these MICs to induce macrophages to produce IL-10 depends on TLR4 internalization from the cell surface. Macrophages subjected to blockade of endocytosis by Dynasore continued to release TNF-α, but failed to produce IL-10, in response to MIC1 or MIC4 exposure. Similarly, IL-10 was not produced by Dynasore-conditioned T. gondii-infected macrophages. Furthermore, MIC1- or MIC4-stimulated macrophages gained transient tolerance to LPS. We report a previously undiscovered mechanism by which well-defined T. gondii components inhibit a host inflammatory response.